Epigenetic transcriptional silencing and 5-azacytidine-mediated reactivation of a complex transgene in rice. - Kumpatla, S P (1997)
Despite a growing number of reports indicating non-Mendelian inheritance of transgene expression in monocots, no detailed description of the structure and stability of the transgene exists for transformants generated by direct DNA-transfer techniques, making the cause for these observations difficult to determine. In this paper we describe the complex organization of Btt cryIIIA and bar transgenes in rice (Oryza sativa L.) that displayed aberrant segregation in R1 progeny. Silencing rather than rearrangement of the bar gene was implicated because the herbicide-sensitive R1 plants had a DNA hybridization profile identical to that of the resistant R0 parent and R1 siblings. Genomic DNA analysis revealed substantial methylation of the Ubi1/bar sequences in silenced plants and, to a lesser degree, in herbicide-resistant plants, suggesting that the transgene locus was potentiated for silencing. Nuclease protection and nuclear run-on assays confirmed that silencing was due to transcriptional inactivation. Treatment of R2 progeny of silenced plants with 5-azacytidine resulted in demethylation of the Ubi1 promoter and reactivation of bar gene expression, demonstrating a functional relationship for methylation in gene silencing. These findings indicate that methylation-based silencing may be frequent in cereals transformed by direct DNA protocols that insert multiple, often rearranged sequences.